Building Models of Their Functions According to SingleValued and Multivalued Compatibility Truth Table of Cryptographic Accelerations (Texas Journal of Engineering and Technology, 2022)
The article describes the features and properties of constructing models of these functions according to the truth table of single-valued and multi-valued cryptographic representations.